A new nanotechnology of fly ash inertization based on the use of silica gel extracted from rice husk ash and microwave treatment. (March 2014) - Bosio, Alberto; Gianoncelli, Alessandra; Zacco, Annalisa; Borgese, Laura; Rodella, Nicola; Zanotti, Davide; Depero, Laura E; Siviero, Giacomo; Cinosi, Amedeo; Bingham, Paul A; Bontempi, Elza
This article reports the first results on chemical stabilization of municipal solid waste incinerator fly ash, by means of the employment of silica gel extracted from rice husk ash. The inertized sample is obtained after thermal treatment by microwave heating. The results of leaching tests on the obtained materials demonstrate that the proposed sol–gel technology is extremely promising in terms of resource used: indeed, all the materials employed for inertization in this treatment are themselves waste materials. The obtained inert material has a composition that makes it extremely interesting for green building applications.